Perceptions of academic discrimination mediate the relationship between political minority status and self-censorship among US college students - Amber R. Grady; Jerome A. Lewis (Discover Psychology)
Abstract According to recent polling, many individuals perceive that universities may limit the freedom of speech of students who hold certain political views. Whereas research has shown that university members who perceive political hostility are more likely to self-censor, few studies have examined how perceived political discrimination affects students’ self-censorship. Thus, this study explored whether perceived political discrimination felt by college students predicts self-censorship in university settings. In Study 1 (N = 163), we found that students who perceived more frequent discrimination reported more self-censorship, regardless of political orientation. In Study 2 (N = 169), we found that Republican students, but not Democrat or Independent students, who believed that they were political minorities at their university were more likely to self-censor if they perceived political discrimination. These findings provide insights into the ongoing discussions about academic freedom and freedom of speech.